New bimetallic compounds based on the bis(thiosemicarbazonato) motif. - Christlieb, M; Cowley, A; Dilworth, JR; Donnelly, P; Paterson, B; Struthers, H; White, J (2007)
Zinc and copper bis(thiosemicarbazonato) complexes containing more than one metal centre have been prepared with a view to examining their application for molecular imaging. The zinc complexes are fluorescent with excitation and emission at relatively long wavelengths. The dinuclear copper complex undergoes two sequential, quasi-reversible reductions.